Competitive amplification of differentially melting amplicons (CADMA) improves KRAS hotspot mutation testing in colorectal cancer - Kristensen Lasse (BMC Cancer, 2012)
Abstract Background Cancer is an extremely heterogeneous group of diseases traditionally categorized according to tissue of origin. However, even among patients with the same cancer subtype the cellular alterations at the molecular level are often very different. Several new therapies targeting specific molecular changes found in individual patients have initiated the era of personalized therapy and significantly improved patient care. In metastatic colorectal cancer (mCRC) a selected group of patients with wild-type KRAS respond to antibodies against the epidermal growth factor receptor (EGFR). Testing for KRAS mutations is now required prior to anti-EGFR treatment, however, less sensitive methods based on conventional PCR regularly fail to detect KRAS mutations in clinical samples. Methods We have developed sensitive and specific assays for detection of the seven most common KRAS mutations based on a novel methodology named Competitive Amplification of Differentially Melting Amplicons (CADMA). The clinical applicability of these assays was assessed by analyzing 100 colorectal cancer samples, for which KRAS mutation status has been evaluated by the commercially available TheraScreen® KRAS mutation kit. Results The CADMA assays were sensitive to at least 0.5% mutant alleles in a wild-type background when using 50 nanograms of DNA in the reactions. Consensus between CADMA and the TheraScreen kit was observed in 96% of the colorectal cancer samples. In cases where disagreement was observed the CADMA result could be confirmed by a previously published assay based on TaqMan probes and by fast COLD-PCR followed by Sanger sequencing. Conclusions The high analytical sensitivity and specificity of CADMA may increase diagnostic sensitivity and specificity of KRAS mutation testing in mCRC patients.